2023
DOI: 10.1152/ajpcell.00054.2023
|View full text |Cite
|
Sign up to set email alerts
|

Passing the post: roles of posttranslational modifications in the form and function of extracellular matrix

Abstract: The extracellular matrix (ECM) is central to the physiology of animal tissues, through its multifaceted roles in tissue structure, mechanical properties and cell interactions, and by its cell-signalling activities that regulate cell phenotype and behaviour. The secretion of ECM proteins typically involves multiple transport and processing steps within the endoplasmic reticulum and the subsequent compartments of the secretory pathway. Many ECM proteins are substituted with various post-translational modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 148 publications
0
5
0
Order By: Relevance
“…Collectively, this is also referred to as the matrisome, which may represent the most ubiquitous group of secreted proteins estimated to account for ∼4% of the human proteome ( 137 ) and comprising approximately 20% of the adult brain volume ( 138 ). The matrisome is abundantly glycosylated but is decorated with multiple other PTMs ( 139 ). For instance, proteomic analysis of ECM-enriched material from pancreatic cells identified 214 matrisomal proteins, where N-glycosylation was detected on 99 proteins, phosphorylation on 18 proteins, and nine proteins carried both PTMs ( 140 ).…”
Section: Post-translational Modifications Of Secretory Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, this is also referred to as the matrisome, which may represent the most ubiquitous group of secreted proteins estimated to account for ∼4% of the human proteome ( 137 ) and comprising approximately 20% of the adult brain volume ( 138 ). The matrisome is abundantly glycosylated but is decorated with multiple other PTMs ( 139 ). For instance, proteomic analysis of ECM-enriched material from pancreatic cells identified 214 matrisomal proteins, where N-glycosylation was detected on 99 proteins, phosphorylation on 18 proteins, and nine proteins carried both PTMs ( 140 ).…”
Section: Post-translational Modifications Of Secretory Proteinsmentioning
confidence: 99%
“…In a study of mouse mammary tumors, 225 unique ECM proteins were identified carrying a total of 229 PTMs that included glycosylation, phosphorylation, and hydroxylation ( 141 ). In fact it is the latter modification that plays an important role in giving the ECM its rigidity, where hydroxylation of proline and lysine residues is carried out by a range of ER-resident enzymes vitally contributing to the maturation and assembly of fibrillar collagen molecules ( 139 ). In addition, lysyl oxidases mediate collagen cross-linking, resulting in stiffening of the ECM, which underlies pathological processes in cancer development by promoting tumor cell invasion and metastasis ( 105 , 142 ).…”
Section: Post-translational Modifications Of Secretory Proteinsmentioning
confidence: 99%
“…The cell processing, composition, and multiscalar combinations of the ECM pose analytical challenges toward evaluating a complete TME that includes the extracellular environment. With the exception of small molecules and minerals, the ECM is primarily composed of proteins with significant contributions from post-translational modifications [46,47]. Post-translational modifications (PTMs) of N-linked glycoproteins and glycosaminoglycans form the basis for gradient control and protein-protein interaction within the ECM PTMs pose analytical challenge through complex structural diversity within glycoform groups, high molecular weight, and a diversity of negatively charged functional groups that can present on the polysaccharides [48,49].…”
Section: Scope Of the Analytical Challengementioning
confidence: 99%
“…Besides proline, lysine also undergoes hydroxylation which stabilizes collagen triple helixes, increases the stiffness and reduces the sensitivity of collagen to proteases [ 88 , 89 ]. Hydroxylation of lysine is catalyzed by lysyl hydroxylase (LH) and most commonly occurs at lysine residues in the Y-position of the Gly-X-Y sequence repeat.…”
Section: Collagen Post-translational Modifications and Their Impact O...mentioning
confidence: 99%
“…Increased hydroxylation of lysine residues within telopeptides by LH2 is associated with fibrotic conditions by increasing collagen crosslinking and stiffness, protecting the collagen from degradation [ 89 ] (Table 3 ). This supports tumor cells by serving as a physical barrier for therapeutics and promoting metastasis [ 88 , 89 , 92 ]. In contrast, hypoxia decreases hydroxylation of lysine residues [ 78 , 93 ].…”
Section: Collagen Post-translational Modifications and Their Impact O...mentioning
confidence: 99%